Sperimentazione dell’ENEA condivisa in remoto per la diffusione di tecnologie innovative di protezione antisismica - Fioriti, Vincenzo; Romano, Roberto; Roselli, Ivan; Tatà¬, Angelo; Colucci, Alessandro; Mongelli, Marialuisa; De Canio, Gerardo (Archeomatica, 2018)
Abstract Within the framework of the CO.B.R.A. project for the development and dissemination of methods, technologies and advanced tools for the conservation of cultural heritage, data and experimental results of several shaking table tests were remotely shared. Through the upgrading of the laboratory with new optoelectronic instrumentation and the application of innovative video processing techniques, the vibrations induced to two typical Italian historic masonry walls and to an isolated pedestal provided with early-warning system for delicate statues were measured and analyzed.